Unexpected tumor reduction in metastatic colorectal cancer patients during SARS-Cov-2 infection. (April 2021) - Ottaiano, Alessandro; Scala, Stefania; D'Alterio, Crescenzo; Trotta, Annamaria; Bello, Annamaria; Rea, Giuseppina; Picone, Carmine; Santorsola, Mariachiara; Petrillo, Antonella; Nasti, Guglielmo
Herein, we describe three patients affected by metastatic colorectal cancer (mCRC) experiencing infection by severe acute respiratory syndrome coronavirus 2 (SARS-Cov-2) and reduction of disease burden during coronavirus disease 2019 (COVID-19) course. Insights into tumor-associated angiotensin-converting enzyme (ACE)-2 expression and lymphocyte function suggest a correlation between host/SARS-Cov-2 infection and tumor burden reduction. This may shed new light into (a) the infection mechanism of SARS-CoV-2 virus and (b) the multiple aspects of a composite antiviral immune response with potential paradoxical and unexpected applications.